Metacognitive Scaffolding in Problem-Based Learning: A Pathway to Developing Higher-Order Thinking Skills - Hutajulu, Masta; Setiyawan, Andri; Yuspriati, Devi Nurul (Department of Mathematics Education Program IPI Garut, 2026)
Kemampuan Berpikir Tingkat Tinggi (HOTS) siswa dalam pembelajaran matematika masih rendah, khususnya pada kemampuan menganalisis, mengevaluasi, dan mencipta. Penelitian ini bertujuan menguji pengaruh Problem-Based Learning yang diperkaya dengan scaffolding metakognitif (PBL-MS) terhadap peningkatan HOTS siswa. Penelitian kuasi-eksperimental dengan desain pretest–posttest control group melibatkan 60 siswa kelas X SMA Negeri 15 Bandung yang dibagi ke dalam kelompok eksperimen (PBL-MS) dan kontrol (PBL). Data kemampuan HOTS dikumpulkan melalui tes tertulis berbentuk esai berdasarkan taksonomi Bloom revisi. Hasil penelitian menunjukkan bahwa peningkatan HOTS siswa pada kelompok PBL-MS berada pada kategori sedang (N-Gain = 0,51), sedangkan kelompok PBL berada pada kategori rendah (N-Gain = 0,30), dengan perbedaan yang signifikan (Sig. 2-tailed < 0,05). Temuan ini menunjukkan bahwa integrasi scaffolding metakognitif dalam PBL lebih efektif dalam meningkatkan kemampuan HOTS siswa. Students’ Higher-Order Thinking Skills (HOTS) in mathematics learning remain low, particularly in analyzing, evaluating, and creating skills, indicating the need for instructional strategies that can better support students’ thinking processes. This study aimed to examine the effect of Problem-Based Learning enriched with metacognitive scaffolding (PBL-MS) on improving students’ HOTS. A quasi-experimental study with a pretest–posttest control group design was conducted at SMA Negeri 15 Bandung, involving 60 tenth-grade students divided into an experimental group (PBL-MS) and a control group (PBL). HOTS data were collected using an essay-based written test developed based on the revised Bloom’s taxonomy, covering analyzing, evaluating, and creating indicators. The results showed that the improvement in HOTS of students taught using PBL-MS was in the moderate category (N-Gain = 0.51), while students taught using PBL alone achieved a low category (N-Gain = 0.30). Statistical analysis indicated a significant difference between the two groups (Sig. 2-tailed < 0.05). These findings indicate that integrating metacognitive scaffolding into Problem-Based Learning provides a stronger effect on improving students’ higher-order thinking skills.